Efforts to Improve Productivity of Paddy (Oryza sativa L.) Var. Inpari 30 by Settings of Planting and Different Cropping Patterns - Aris Ermanto; Agus Suryanto; Didik Hariyono (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2021)
Solar radiation is an essential factor in the process of plant metabolism. Indonesia has a rainy season and the dry season, which causes differences in solar radiation intensity. The purpose of this study was to obtain information on suitable planting times and optimal cropping patterns for rice in the dry season in an effort to increase plant productivity. The study was conducted using a nested design, with two factors. The first factor is planting time. The second factor is cropping pattern, a nested factor in planting time that consists of 3 levels of cropping pattern (CP). These experiments have six combinations, and these experiments were repeated three times. Cropping pattern of jajar legowo 40 cm x 20 cm x 12.5 cm can give the best results on the parameters of leaf area index, plant growth rate, percentage of productive tillers, weight per square meter and rice productivity. Rice productivity is greatly influenced by planting time and cropping patterns. The planting time in September produced the highest productivity, reaching 6.99 t ha-1. While rice planted with jajar legowo cropping patterns (40 cm x 20 cm x 12.5 cm) had productivity up to 7.66 t ha-1.